Sugarcane Root Transcriptome Analysis Revealed the Role of Plant Hormones in the Colonization of an Endophytic Diazotroph - Nong, Qian; Malviya, Mukesh Kumar; Solanki, Manoj Kumar; Solanki, Anjali Chandrol; Lin, Li; Xie, Jinlan; Mo, Zhanghong; Wang, Zeping; Song, Xiu-Peng; Huang, Xin; Rai, Shalini; Li, Changning; et al. (Frontiers in Microbiology, 2022)
Abstract: Some sugarcane germplasms can absorb higher amounts of nitrogen via atmospheric nitrogen fixation through the bacterial diazotrophs. Most endophytic diazotrophs usually penetrate through the root, colonize inside the plant, and fix the nitrogen. To assess the plant's bacterial association during root colonization, strain GXS16 was tagged with a plasmid-bear green fluorescent protein (GFP) gene. The results demonstrated that the strain can colonize roots all the way to the maturation zone. The strain GXS16 showed maximum nitrogenase enzyme activity at pH 8 and 30 °C, and nitrogenase activity is less affected by different carbon sources. Further, strain GXS16 colonization response was investigated through plant hormones analysis and RNAseq. The results showed that the bacterial colonization gradually increased with time, and the H2O2 and malondialdehyde (MDA) content significantly increased at 1 d (day) after inoculation. There were no substantial changes noticed in proline content, and the ethylene content was detected initially, but it decreased with time. The abscisic acid (ABA) content showed significant increases of 91.9%, 43.9%, and 18.7%, but conversely, the gibberellin (GA3) content decreased by 12.9%, 28.5%, and 45.2% at 1 d, 3 d and 5 d after inoculation, respectively. The GXS16 inoculation significantly increased the activities of catalase (CAT), superoxide dismutase (SOD), polyphenol oxidase (PPO), ascorbate peroxidase (APX) and glutathione reductase (GR) at different timepoint. In contrast, the peroxisome (POD) activity had no changes detected during the treatment. In the case of RNAseq analysis, 2437, 6678, and 4568 differentially expressed genes (DEGs) were identified from 1 d, 3 d and 5 d inoculated root samples, and 601 DEGs were shared in all samples. The number or the expression diversity of DEGs related to ethylene was much higher than that of ABA or GA, which indicated the critical role of ethylene in regulating the sugarcane roots response to GXS16 inoculation.